2014
DOI: 10.1007/s11295-014-0709-1
|View full text |Cite
|
Sign up to set email alerts
|

A consensus ‘Honeycrisp’ apple (Malus × domestica) genetic linkage map from three full-sib progeny populations

Abstract: The apple cultivar Honeycrisp is emerging in North American markets due to its outstanding eating quality. A set of three 'Honeycrisp' progeny populations from the University of Minnesota apple breeding program were utilized to construct parental and consensus 'Honeycrisp' linkage maps to enable marker-assisted breeding. Two populations were segregated for fruit texture traits and a third was of interest in examining disease resistance. All available individuals were genotyped with the International RosBREED S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This might be the case between the genotypes used for the draft genome sequence and the parents used in this study and might explain the differences observed between the genetic and physical map found. Undoubtedly, a consensus genetic map for cassava could be helpful in this regard, as has been performed for other species with high heterozygosity level such as grapevine and apple [ 78 , 79 ]. Other explanations might be that some of the markers identifying these scaffolds are not properly mapped or because of errors during assembly of the reads, that are still present in the draft genome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the case between the genotypes used for the draft genome sequence and the parents used in this study and might explain the differences observed between the genetic and physical map found. Undoubtedly, a consensus genetic map for cassava could be helpful in this regard, as has been performed for other species with high heterozygosity level such as grapevine and apple [ 78 , 79 ]. Other explanations might be that some of the markers identifying these scaffolds are not properly mapped or because of errors during assembly of the reads, that are still present in the draft genome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic maps were constructed in JOINMAP 4.1 software (Van Ooijen 2006 , 2011 ) using 165 progeny from a cross between ‘FL_08-10’ × ‘12.115-10’ and 91 progeny from ‘Winter Dawn’ × ‘Treasure.’ The markers were curated to achieve consistent performance across the germplasm, to maximize polymorphism and to exclude markers with fraction values of observed (oDR) and expected (eDR) double recombination singletons > 0.05 (Clark et al 2014 ). Subgenomes and orientations of linkage groups were assigned according to van Dijk et al ( 2014 ) as the maps share many common markers with those described in Bassil et al ( 2015 ) and Mangandi et al ( 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…These three projects utilized the Illumina® Infinium® genotyping platform. To date, these arrays have been used for the generation of linkage maps [ 4 , 6 - 11 ], evaluation of the quality of physical maps [ 12 ], fine mapping and validation of quantitative trait loci (QTL) [ 9 , 13 ], elucidation of marker-trait associations [ 10 , 14 ], genome-wide association studies [ 15 ], genomic selection studies [ 16 ], validation of pedigrees and verification of trueness to type of breeding lines and accessions [ 17 ], and for design of the future generation of arrays [ 18 ]. Thus, these three arrays have had broad utility for the Rosaceae genomics and genetics research and breeding communities.…”
Section: Introductionmentioning
confidence: 99%